Librarian's role in dentistry systematic reviews: an epidemiologic study (Perspectivas em Ciência da Informação, 2023)
Objective:  Identify the librarian presence in dentistry systematic reviews. The primary outcome was the frequency and role of librarian presence. The secondary outcomes were to assess whether there are differences regarding impact factor, strategy availability, number of databases, and registration of protocol, in the systematic reviews that included or not a librarian. Methods: It were included systematic reviews in dentistry, in English, published in dental journals, indexed from July 1st, 2018 to July 1st, 2019 available on MEDLINE/PubMed. For statistical analysis, the T-test and Pearson's chi-squared test were used. The significance level was 5%. Results: Among 280 included studies 14% systematic reviews mention librarian participation, 9% as consultants and 5% as co-authors. There was no statistical difference for impact factor (p=0.928) outcomes, search strategy available (p=0.850), and number of database (p=0.240) among the studies that had or not the presence of the librarian. The number of systematic reviews registered was higher when the librarian was present. The databases mentioned more frequently were MEDLINE, Cochrane, and Embase. Conclusion: The frequency of librarian participation in the included systematic reviews was 14%. The most frequent participation was as consultants. Systematic reviews with a librarian on the team were associated with more protocol registration.